Strategi Pengembangan Pariwisata DiPulau Sara Berbasis Smart and Fun - mepilani_tulis tulis; Louis Kandoli; Telly Tangkere (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
The study aims to identify a tourism development strategy based on the Smart and Fun concept as a result of the adaptation of Smart Tourism and Edu-CoTourism. The method used is qualitative with SWOT analysis technique as a technique used to analyze indicators of internal-external factors that affect the status of progress of tourist destinations on the Sara'a island. The results of the research are Internal Strength factor's result is 1.91, the Weakness weight is 0.95, for the external Opportunities factor has a weight 1.74 and the Threast has 1.06 so from these results it can be concluded that the weakness of the internal factor has no dominant influence on the development of tourist destination. Supported by opportunities generated from external factors, the Smart and Fun concept strategy could be considered as an innovation and creative strategy for the development of tourist destination on the Sara'a island. Based on the IFAS-EFAS diagram, the Smart and Fun concept strategy is included in coordinate I, which means that the strategy could be progressively operated.